Loss‐of‐function mutation of serine racemase attenuates excitotoxicity by intravitreal injection of N‐methyl‐D‐aspartate. Issue 1 (13th November 2015) - Jiang, Haiyan; Wang, Xianwei; Zhang, He; Chang, Yuhua; Feng, Meiling; Wu, Shengzhou
Abstract: Convincing data demonstrate that D‐serine, a racemized product of serine racemase (SR), contributes to neurotoxicity. Furthermore, a line of evidence suggests that SR/D‐serine contributes to retinal neurodegeneration in a diabetic retinopathy rat model and diabetic retinopathy patients. However, the connection between SR/D‐serine and retinal neurodegeneration remains unclear. Herein, we report that intravitreal injection of N ‐methyl‐D‐aspartate (NMDA) induces excitotoxicity in rodent retina; this retinal neurodegeneration was attenuated in retina carrying a loss‐of‐function of mutation in Srr, the gene for SR, termed Srr ochre 269 . Under the condition of NMDA injection, either posterior pole or middle – but not peripheral – retina from Srr ochre 269 mice was found to retain more retinal ganglion cells (RGC) than the counterpart from w/t (RGCs were identified with retrograde labeling). Terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) staining further demonstrated reduced RGC apoptosis from Srr ochre 269 compared to w/t mice under the condition of NMDA injection. Collectively, our studies demonstrate a pivotal role of SR/D‐serine in retinal neurotoxicity. We demonstrated that loss‐of‐function mutation of the gene encoding serine racemase significantly attenuates excitotoxicity in retina; excitotoxicity accounts for retinal ganglion cell (RGC) demise in diabetic retinopathy (DR). We think that our findings deepen the current knowledge of the mechanisms of RGC degeneration. Abstract : We demonstrated that loss‐of‐function mutation of the gene encoding serine racemase significantly attenuates excitotoxicity in retina; excitotoxicity accounts for retinal ganglion cell (RGC) demise in diabetic retinopathy (DR). We think that our findings deepen the current knowledge of the mechanisms of RGC degeneration.